2018
DOI: 10.1515/aoas-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Parameters of Selected Internal Organs of Fattening Pigs and Wild Boars

Abstract: The objective of the study was to analyse selected physical properties and chemical indicators of internal organs obtained from fattening pigs and Central European wild boars (Sus scrofa scrofa). Each group consisted of 12 animals. The tongue, heart, lungs, liver and kidneys were examined for physical properties, basic chemical composition, macro- and micromineral content, and fatty acid profile. The atherogenic index (AI) and the thrombogenic index (TI) were also determined. Pig offal was found to be a rich s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…Unlike domestic pigs, wild boars are characterised with a greater proportion of by products in their body weight. In their study, Babicz et al [24] found that the proportion of tongue, heart, liver and kidneys in the body of 113.6-115.3 kg fatteners corresponds to 0.26%, 0.37%, 1.41% and 0.15%. On the other hand, Migdał et al [25] presented an even higher proportion of internal organs in the body weight of 110 kg fatteners, measuring 0.36-0.41% for the heart, 2.04-2.17% for the liver and 0.36-0.43% for the kidneys.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Unlike domestic pigs, wild boars are characterised with a greater proportion of by products in their body weight. In their study, Babicz et al [24] found that the proportion of tongue, heart, liver and kidneys in the body of 113.6-115.3 kg fatteners corresponds to 0.26%, 0.37%, 1.41% and 0.15%. On the other hand, Migdał et al [25] presented an even higher proportion of internal organs in the body weight of 110 kg fatteners, measuring 0.36-0.41% for the heart, 2.04-2.17% for the liver and 0.36-0.43% for the kidneys.…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, Drozd et al [23] found different dressed field weights of wild boars hunted in Poland: juveniles weighted 29.0 kg, yearlings weighted 48.9 kg, while the adults weighted 83.9 kg. Babicz et al [24] studied the proportion of internal organs in the dressed filed weight of wild boars (51.9-54.3 kg). These authors found a higher proportion of heart (0.79%) and kidneys (0.57%), and lower proportion of tongue (0.43%) in the body weight of wild boars, compared to our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, due to greater consciousness about the influence of food on human health, the interest of modern consumer in game meat is enhancing (Soriano et al 2006). The natural, slow growth of game animals and the nutrition based on natural feed results in lighter carcases, but also in the development of high quality meat (Babicz et al 2018). The acquisition of wild animals does not affect the environment, and is not related to welfare concerns like animal farming.…”
Section: Introductionmentioning
confidence: 99%